2023
DOI: 10.3390/en16186475
|View full text |Cite
|
Sign up to set email alerts
|

Tight and Shale Oil Exploration: A Review of the Global Experience and a Case of West Siberia

Desmond Batsa Dorhjie,
Elena Mukhina,
Anton Kasyanenko
et al.

Abstract: Shale and tight oil reservoirs, with horizontal wells and hydraulic fractures, typically have a recovery ratio of around 10%. The exploration of tight oil and shale in North America has proven economically viable, thanks to advancements, such as horizontal wells, hydraulic fracturing, and other enhanced oil recovery techniques. Taking inspiration from the global experience (the North American shale experience), the exploration and development of the West Siberian tight and shale reserves was more focused on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…Shale oil is typically developed through horizontal wells with volumetric hydraulic fracturing, but there are problems, such as rapid production decline and low recovery after a period of production. At present, the shale oil recovery factor under this technology is generally less than 10%. The low permeability and porosity of shale reservoirs present hindrances to conventional water and chemical flooding methods. Moreover, the gas flooding process in fractured shale reservoirs is plagued by the significant issue of viscous fingering, leading to low sweep efficiency and the propensity for gas channeling .…”
Section: Introductionmentioning
confidence: 99%
“…Shale oil is typically developed through horizontal wells with volumetric hydraulic fracturing, but there are problems, such as rapid production decline and low recovery after a period of production. At present, the shale oil recovery factor under this technology is generally less than 10%. The low permeability and porosity of shale reservoirs present hindrances to conventional water and chemical flooding methods. Moreover, the gas flooding process in fractured shale reservoirs is plagued by the significant issue of viscous fingering, leading to low sweep efficiency and the propensity for gas channeling .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the exploitation of unconventional reservoirs with abundant resources has drawn extensive attention, resulting from the rapid innovation of horizontal drilling and fracturing technology. Among unconventional reservoirs, tight oil reservoirs have become crucial substitute petroleum resources for covering the resource shortage of conventional oil reservoirs. Practically, it has been reported that volumetric fracturing technology offers advantages in reservoir reconstruction, improving the flow conductivity and enhancing the extraction efficiency of petroleum resources. Slick water fracturing, as the main system supporting volumetric fracturing technology, is capable of improving the pump injection volume and reducing the friction of a pipe wall . Therein, the polyacrylamide (PAMs) drag reducer is the most crucial additive in slick water fracturing for enhancing the reservoir reconstruction result. , …”
Section: Introductionmentioning
confidence: 99%